2002
DOI: 10.1006/bare.2002.0190
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Management Induced by Cognitive Reference Points

Abstract: Previous studies (Carslaw, 1988;Thomas, 1989;Niskanen & Keloharju, 2000) have shown that companies' managers tend to round-up the ®rst digits of reported earnings (i.e. for companies reporting pro®ts). According to Carslaw (1988), this type of behaviour is inspired by the existence of the so-called`$1Á99' phenomenon where a price of $1Á99 is perceived as being abnormally lower than one of $2Á00. In the current study, we try to determine whether managers of UK-listed companies also engage in this type of`earnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 22 publications
11
51
0
7
Order By: Relevance
“…Newcomb (1881) and later Benford (1938) noted that in a sufficiently large collection of numerical data expressed in a decimal form, the distribution of occurrences of first digits is not uniform (we explain Benford's distribution in more detail in section 2). Many authors, including Carslaw (1988), Guan et al (2006), Kinnunen and Koskela (2003), Nigrini (2005), Niskanen and Keloharju (2000), Skousen et al (2004), Thomas (1989) and Van Caneghem (2002, 2004 investigated the applicability of this fact in accounting and auditing, and specifically in the detection of "cosmetic earning management". It has been shown that the distribution of first digits in financial reports normally complies with Benford's law.…”
mentioning
confidence: 99%
“…Newcomb (1881) and later Benford (1938) noted that in a sufficiently large collection of numerical data expressed in a decimal form, the distribution of occurrences of first digits is not uniform (we explain Benford's distribution in more detail in section 2). Many authors, including Carslaw (1988), Guan et al (2006), Kinnunen and Koskela (2003), Nigrini (2005), Niskanen and Keloharju (2000), Skousen et al (2004), Thomas (1989) and Van Caneghem (2002, 2004 investigated the applicability of this fact in accounting and auditing, and specifically in the detection of "cosmetic earning management". It has been shown that the distribution of first digits in financial reports normally complies with Benford's law.…”
mentioning
confidence: 99%
“…Their study and others (e.g. van Caneghem, 2002) have indicated that some minor massaging of figures does take place in order to reach significant reference points.…”
Section: Techniques Of Creative Accountingmentioning
confidence: 89%
“…Later on, Thomas (1989) confirms the existence of rounding up behaviour of listed companies in United States of America (USA). Subsequently, other studies like Shette and Kuntluru (2014) in India, Skousen et al (2004) in Japan, Niskanen aand Kelhoharju (2000) in Finland, Kinnunen and Koskela (2003) across eighteen different countries, Caneghem (2002) and Caneghem (2004) in United Kingdom find rounding up behavior in the reported income of listed companies. However, no study till date has focused on examining the quality of reported incomes of unlisted companies based on Benford"s Law.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 94%